Influence of vegetation structure on the diversity and distribution of nocturnal insects in oil palm plantations of Central Kalimantan - Savitri, Shanty; Fajri, Samsul; Araina, Elga; Basuki, Bejo; Haryono, Agus; Fahrina, Ririn; Fatiqin, Awalul; Kioumarsi, Hamed (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Environmental changes caused by oil palm plantation activities can affect the diversity of nocturnal insects that play important roles in the ecosystem as pollinators, decomposers, predators, and food sources for other insects as well as bioindicators. This study aimed to determine the levels of diversity, evenness, and dominance of nocturnal insects at two stations with different oil palm planting ages in Seruyan Regency. This study used a descriptive quantitative approach with an exploratory survey method. Nocturnal insects were collected from replanting and non-replanting oil palm areas using light traps equipped with UV lamps. The insects were identified to the species level, and data were analyzed using the Shannon–Wiener diversity index (H′), Pielou’s evenness index (E), and Simpson’s dominance index (C) with the PAST software. The results showed that from a total of 454 individuals, 15 species of nocturnal insects were successfully identified, originating from 6 orders, namely, Coleoptera (Laccophilus gentilis, Protaetia acuminata, Pangaeus bilineatus, Adoretus versutus, Denticollis linearis, Eumorphus bulbosus, Sirthenea flavipes, Cicindela gallica), Hymenoptera (Vespa affinis, Tetraponera rufonigra), Hemiptera (Pangaeus bilineatus), Odonata (Agriocnemis pygmaea), Lepidoptera (Hypochrosis subrufa, Chytolita morbidalis), and Orthoptera (Gryllus assimilis). The most dominant species was Pangaeus bilineatus with 143 individuals, while the species with the lowest number of individuals was Cicindela gallica with 3 individuals. The Shannon‒Wiener diversity index (H') value of 1.558 (Station I) and 2.129 (Station II) indicates moderate diversity, the Pielou evenness index (E) value of 0.59 (Station I) and 0.65 (Station II) indicates a fairly even distribution, and the Simpson dominance index (C) value of 0.72 (Station I) and 0.85 (Station II) indicates no extreme species dominance. The study revealed moderate nocturnal insect diversity with balanced species distribution, indicating a stable oil palm ecosystem and supporting their role as bioindicators of ecological health.